Influence of a hydrothermal system on ground deformation during volcanic eruption - Zarin, Gleb Aleksandrovich; Melnik, Oleg Eduardovich; Tsvetkova, Yulia Dmitrievna; Afanasyev, Andrey Aleksandrovich (Computational Continuum Mechanics, 2015)
Ground deformation measurement is one of the major ways to monitor active volcanoes. Processes in a magma chamber-conduit system as well as in geothermal systems heated by the ascending magma are the main sources of ground deformation. Influence of magma chambers and volcanic conduits on ground deformation is widely investigated theoretically, but there are no studies on ground deformation that is associated with short-term changes in a hydrothermal system during a volcanic eruption. Two patterns of ground deformation caused by changes in pressure in a volcanic conduit and by high temperature hydrothermal systems are compared in the paper. It is shown that vertical displacements related to the activity of a hydrothermal system can be several times larger than those initiated by magma flows. Ground deformation patterns are significantly different for these sources. In the case of a hydrothermal system the induced maximum of the vertical displacement is located above the conduit. There is a local surface subsidence above the conduit at deformations induced by conduit processes. The maximum surface uplift is observed at a distance approximately twice the depth of the upper part of the conduit. The influence of a hydrothermal system should be considered in the interpretation of monitoring data of active volcanoes.